THE INFLUENCE OF WOMEN'S ENTREPRENEURIAL SKILLS ON ECONOMIC INDEPENDENCE WITH PRODUCT INNOVATION AS MODERATING VARIABLE (CASE STUDY: HOME INDUSTRY MEDAN CITY) - Merry Moy Mita; Farina Jessen YAP (Program Sarjana Manajemen Universitas Internasional Batam, 2025)
The study examines the multifaceted relationship between women's entrepreneurial skills, product innovation, and economic independence within the home industry sector of Medan City. Utilizing a quantitative descriptive approach, data were gathered from a purposive sample of 376 women entrepreneurs. Questionnaires were distributed both offline and online, and the collected data were analyzed using Structural Equation Modeling-Partial Least Square (SEM-PLS) with Smart PLS 4.0 software. The analysis process included rigorous testing for validity and reliability, as well as an evaluation of both the measurement and structural models to ensure the robustness of the findings. The results reveal that entrepreneurial skills possess a statistically significant influence on product innovation, demonstrating that a high level of managerial, leadership, and creative abilities among female entrepreneurs directly enhances their capacity to innovate. Furthermore, a strong and significant relationship was found between product innovation and economic independence, indicating that diversifying products increases competitive advantage and improves financial security. Crucially, the analysis confirms that product innovation acts as a significant mediator in the link between entrepreneurial skills and economic independence. This finding highlights that entrepreneurial skills are most effective in promoting economic independence when consistently accompanied by product innovation. The most dominant indicators were leadership skills, product variants, and financial management capabilities, which are identified as key drivers of success. In conclusion, this research underscores the vital role of product innovation in translating entrepreneurial talent into tangible economic empowerment for women in the home industry.